PERTUMBUHAN BIBIT KAKAO (Theobroma cacao.L) PADA MEDIA SUBSOIL ULTISOL DENGAN PEMBERIAN PUPUK NPKMg DAN PUPUK KANDANG AYAM - Makarios Butar Butar; Balonggu Siagian; Irsal Irsal (Jurnal Agroekoteknologi, 2013)
ABSTRACTGrowth of Cocoa Seedlings (Theobroma cacao.L) In Media Ultisol Subsoil with FertilizerProvision NPKMg(15:15:6:4) and Manure. This research aims to determine the effect of manureand fertilizier NPKMg(15:15:6:4) on the growth of cocoa (Theobroma cacao.L) in media landultisol subsoil. Research carried out in field trials USU Faculty of Agriculture, Medan with altitudeof about 25 meters above sea level at the beginning of November until March 2012. Experimentalmethod use is a randomized block design with two treatment factor. Planting media as the firstfactor with five standard treatment that is 0% Manure + 100% Ultisol Subsoil, 25% Manure + 75%Ultisol Subsoil, 50% Manure + 50% Ultisol Subsoil, 75% Manure + 25% Ultisol Subsoil, 100%Manure + 0% Ultisol Subsoil and fertilizer NPKMg(15:15:6:4) as the second factor with four levelis 0 g/polibag, 4 g/polibag, 8 g/polibag and 12 g/polibag with 3 replications. Parameter wereobserved at high parameters of shoots, girth, number of leaves, the aweight of wet canopy, wetweight of roots, canopy dry weight, and root dry weight. The results that 75% Manure + 25%Ultisol Subsoil showed the best results at high parameters of shoots, girth, number of leaves, theaweight of wet canopy, wet weight of roots, canopy dry weight, and root dry weight. NPKMgfertilizier(15:15:6:4) in this study showed significant results in all parameters, but obtained at thehighest treatment level 8 g/polibag and 12 g/polibag. The interaction effect was not significanteffect on all parameters.Keywords: manure, NPKMg fertilizer, Theobroma cacao.L .poultry manure